Behavioural factors associated with cigarette quitting behaviour: an analysis of cross-sectional survey data collected in three low-income South African communities - Laura Rossouw; Samantha Filby (BMJ Open)
Objective To study the behavioural factors associated with sustained cigarette smoking cessation, and those associated with a current smoker attempting to quit, among current and former cigarette smokers living in low-income South African communities.Setting Three low-income areas in South Africa.Design In-person surveys with structured questions that asked respondents about their cigarette smoking and quitting behaviour, sociodemographic information and behavioural attributes.Participants Current smokers were eligible to participate if they had smoked at least one cigarette in the week prior to the interview (n=569). Former smokers were eligible if they had ever smoked cigarettes regularly in the past and had abstained from smoking for at least 6 months (n=106).Outcomes (1) Abstinence from cigarette smoking for at least 6 months and (2) attempting to quit cigarette smoking in the past 12 months.Results Compared with low levels of self-control, high levels of self-control increase the odds of sustained cessation (OR=2.690, 95% CI: 2.480 to 2.917) and of making a quit attempt (OR=1.271, 95% CI: 1.254 to 1.288). Relative to low levels of stress, high levels of stress reduce the odds of sustained cessation (OR=0.938, 95% CI: 0.927 to 0.948) and of attempting to quit (OR=0.824, 95% CI: 0.666 to 1.019). Hyperbolic discounting reduces the odds of sustained cessation (OR=0.841, 95% CI: 0.822 to 0.862) while exhibiting more quitting self-efficacy increases these odds (OR=2.063, 95% CI: 1.745 to 2.439). Being impatient reduces the odds of making a quit attempt (OR=0.814, 95% CI: 0.702 to 0.943), as does a tendency to postpone important tasks (OR=0.784, 95% CI: 0.644 to 0.956).Conclusions Non-pharmacological cessation support to low-income smokers should challenge potential lifetime quitters to practice self-control, equip them with tools to manage stress, and tackle temptations to time-discounting. Existing healthcare infrastructure should be leveraged to question people who smoke about their behavioural attributes, and to use this information to deliver behavioural support that motivates and facilitates sustained smoking cessation.